Supply Chain Project Management. - Ayers, James B. (CRC Press, 2009)
A guide to implementing strategic supply chain improvements. It describes the benefit of applying project management skills to improve collaboration and communication among one's own company and its suppliers and customers. It explains how to achieve company-wide agreement for developing and directing various strategies.